A brief history of early Okinawa based on the Omoro sōshi - Sakihara, Mitsugu 1928-2001 (Center for Okinawan Studies, University of Hawaiʻi at Mānoa, 2024)
"Mitsugu Sakihara introduced the English-speaking world to the wonders of the Omoro Sōshi, a collection of Old Okinawan poetry, when he published the original version of A Brief History of Early Okinawa Based on the Omoro Sōshi in 1987. The omoro poems, numbering some 1500 or so in total, were compiled between 1532 and 1610, the Golden Age of Okinawan (and Ryukyuan) political, economic, and cultural wherewithal. The poems offer, through the careful analysis that Sakihara employed, some challenges to the sanitized official histories compiled during the period, providing insights into the "real-life" circumstances of the people, places, and (sometimes jarringly violent) actions from the early history of the late island kingdom. Details about historical figures emerge, encomiums are issued regarding rulers and the seats they ruled from, life and daily activities in the villages are addressed, the role of the noro priestesses in the national life is celebrated, ships are launched to far-flung places, and prayers are offered; the whole of that rich historical period comes to life in this work by an esteemed scholar. This reissue of Sakihara's classic work comes on the heels of the recent scholarship that builds on the themes that he addressed more than three decades ago. Those, of course, are not to be discounted, but A Brief History reminds us of the debt we owe to the pioneering work of Mitsugu Sakihara."